CALCULATION OF COST OF PRODUCTION FOR DETERMINING BASIC SELLING PRICES IN THE NEW FLEET CAROSERY COMPANY, MALANG (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
ABSTRACT Nowadays, the need for public transportation is very necessary. This is the reason that public transportation in Indonesia is increasing because the need for public transportation is very necessary for a country that is ready to develop, like Indonesia, which is currently developing its means of transportation. various vehicles that are very necessary, in this case the types of private vehicles that are ranked first or highest for domestic market demand. With the development of the times in Indonesia, various types of commercial vehicles have been able to become private vehicles. With the increasing demand for commercial vehicles to become private vehicles. Due to the increasing demand for vehicles, this has led to the development of the car body industry in our country. This situation results in competition between the car body industry, companies must carry out calculations or analyzes of the opinions they will obtain and the costs used to obtain these revenues. In this case, the placement of the cost of production plays a very important role. In the process of preparing the cost of production, it is necessary to pay attention that each component must be calculated correctly and the assignment is very precise, so that the reliability of the accuracy of the cost of production as cost information is not misleading and can be accounted for. Therefore, it is necessary to calculate the cost of production as a basis for determining the selling price for the New Armada Malang bodywork Keywords: Cost of Goods Production, Basis for Determination, Selling Price